2017
DOI: 10.1155/2017/4927964
|View full text |Cite
|
Sign up to set email alerts
|

Group 2 Innate Lymphoid Cells Are Involved in Skewed Type 2 Immunity of Gastric Diseases Induced by Helicobacter pylori Infection

Abstract: H. pylori induces a complicated local and systematic immune response and contributes to the carcinogenesis of gastric cancer. A primary type 1 immune response is evoked by H. pylori since its occurrence. However, it is not unusual that an inhibitory immunity is dominant in H. pylori-associated diseases, which are promoted by the formation of immunosuppressive microenvironment. But whether group 2 innate lymphoid cells (ILC2s) plays a critical role in H. pylori-induced skewed type 2 immunity is still unclear. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…It is still unknown whether there are generalized suppressive mechanisms to limit ILC2 activation, such as regulatory ILCs (ILCregs) that produce IL-10, or conversion into different types by cytokines such as IL-27 and IL-12. These considerations are quite important due to the major role of ILC2 in the context of health and disease [12,34]. In particular, understanding how ILC2s are regulated in the context of a helminth infection will be necessary for improving existing anthelmintic drugs and developing new therapeutics to treat helminth infections.…”
Section: Regulation Of Ilc2mentioning
confidence: 99%
“…It is still unknown whether there are generalized suppressive mechanisms to limit ILC2 activation, such as regulatory ILCs (ILCregs) that produce IL-10, or conversion into different types by cytokines such as IL-27 and IL-12. These considerations are quite important due to the major role of ILC2 in the context of health and disease [12,34]. In particular, understanding how ILC2s are regulated in the context of a helminth infection will be necessary for improving existing anthelmintic drugs and developing new therapeutics to treat helminth infections.…”
Section: Regulation Of Ilc2mentioning
confidence: 99%
“…Li et al . reported an increase in Lin + GATA3 + as well as Lin − GATA3 + ILC2‐like populations together with a more pronounced type 2 signature limiting the protective type 1 immune response in the development of cancers . In mice , Helicobacter typhlonius infection triggers IL‐17A expressing ILCs by synergizing DCs derived TNF‐α and IL‐23 in the Tbx21 −/− Rag2 −/− ulcerative colitis (TRUC) model …”
Section: Microbiota – Ilc Axis During Infectious Diseasesmentioning
confidence: 99%
“…We then investigated which elements of the conceivable molecule mechanism H. pylori brought to vascular endothelial cells. According to our previous study, an increased expression of GATA3 induced by H. pylori might participate in skewed type-2 immune responses [35], which suggested that the increase of GATA3, induced by H. pylori , has the potential to effect more than just the stomach. Reduced GATA3 levels of Th2 responses induced a regression of atherosclerosis and other inflammatory diseases [18,36].…”
Section: Discussionmentioning
confidence: 99%